Unraveling the Controls on Snow Disappearance in Montane Conifer Forests Using Multi‐Site Lidar. Issue 12 (20th December 2021) - Safa, H.; Krogh, S. A.; Greenberg, J.; Kostadinov, T. S.; Harpold, A. A.
Abstract: Snow disappearance date (SDD) affects the ecohydrological dynamics of montane forests, by altering water availability, forest fire regime, and the land surface energy budget. The forest canopy modulates SDD through competing processes; dense canopy intercepts snowfall and enhances longwave radiation while shading snowpack from shortwave radiation and sheltering it from the wind. Limited ground‐based observations of snow presence and absence have restricted our ability to unravel the dominant processes affecting SDD in montane forests. We apply a lidar‐derived method to estimate fractional snow cover area (fSCA) at two relatively warm sites in the Sierra Nevada and two colder sites in the Rocky Mountains, which we link to SDD. With the exception of late season snowpack and low fSCA, snow retention is longer under low vegetation density than under high vegetation density in both warm and cold sites. Warm forests consistently have longer snow retention in open areas compared to dense under canopy areas, particularly on south‐facing slopes. Cold forests tend to have longer snow retention under lower density canopy compared to open areas, particularly on north‐facing slopes. We use this empirical analysis to make process inferences and develop an initial framework to predict SDD that incorporates the role of topography and vegetation structure. Building on our framework will be necessary to provide better forest management recommendations for snowpack retention across complex terrain and heterogenous canopy structure. Plain Language Summary: The timing of snow disappearance is an important control of the amount and timing of water available for forest ecosystems and downstream communities. In forested areas, trees intercept snowfall which decreases snow accumulation, but they also shade the snowpack from the sun and reduce wind, which lengthens snow retention. Warm trees also emit thermal radiation that can melt the snowpack near the canopy. Competition among these factors causes different snow disappearance timing in open areas versus under tree canopy. We use light detection and ranging (lidar) measurements to quantify snow presence or absence in the open and below the forest canopy. The results show that snow disappears earlier under dense forest canopy than in open areas at warmer sites, especially on south‐facing slopes that receive more sunlight. In contrast, colder sites tend to retain snow longer under a tree canopy than open areas, especially on north‐facing slopes. However, lower elevations of colder sites can behave more like warmer sites by retaining snow longer in open areas. This unique multi‐site snow dataset suggests that tree canopy removal would have greater benefit for retaining snow longer at warm sites than at cold sites, although additional refinement is needed. Key Points: Lidar dataset shows the interacting role of climate, topography, and conifer forest structure in open versus under canopy snow disappearance Warm forests consistently have longer snow retention in open areas, particularly compared to areas under the dense canopy on south‐facing slopes Cold forests tend to have longer snow retention under lower density canopy compared to nearby open areas, particularly on north‐facing slopes